A Concise Route to Cyclic Amines from Nitroarenes and Ketoacids under Iron‐Catalyzed Hydrosilylation Conditions. Issue 15 (3rd July 2021) - Wu, Jiajun; Tongdee, Satawat; Ammaiyappan, Yuvaraj; Darcel, Christophe
Abstract: Starting from nitroarenes, under hydrosilylation conditions, using a well‐defined N ‐heterocyclic carbene iron(0) catalyst, (IMes)Fe(CO)4, the corresponding aniline derivatives were produced in 61–92% isolated yields. More impressively, a selective synthesis of cyclic amines such as pyrrolidines, piperidines and azepanes were conducted from levulinic acid, 1, 5‐ and 1, 6‐keto acids, respectively. The sequential procedure proceeded under both visible light irradiation and thermal conditions with 20 examples in isolated yields up to 69%. Abstract :